2012
DOI: 10.1093/rheumatology/kes225
|View full text |Cite
|
Sign up to set email alerts
|

Primary anti-phospholipid syndrome: any role for serum complement levels in predicting pregnancy complications?

Abstract: No association was found between hypocomplementaemia and obstetric complications in PAPS. However, both cases of pre-eclampsia were characterized by low C3 throughout pregnancy. There is evidence that the complement system is a contributor to the mechanisms of aPL-mediated damage, but its predictive role on the final pregnancy outcome does not seem to be of major impact.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 12 publications
1
26
0
Order By: Relevance
“…Previous studies have demonstrated that the activation of complement components C3, C4, and C5 increases the risk of injury or death in animal models injected with aPL ( 16 , 17 ). Our group has also investigated this relationship in a multicenter study ( 18 ). Utilizing pregnancy C3 and C4 normality ranges (in each trimester), we did not show an association between hypocomplementemia and obstetric complications in primary APS.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that the activation of complement components C3, C4, and C5 increases the risk of injury or death in animal models injected with aPL ( 16 , 17 ). Our group has also investigated this relationship in a multicenter study ( 18 ). Utilizing pregnancy C3 and C4 normality ranges (in each trimester), we did not show an association between hypocomplementemia and obstetric complications in primary APS.…”
Section: Discussionmentioning
confidence: 99%
“…Even if our study was performed in few patients, higher CD8+DR+ T-cell percentages were an independent risk factor for development of complications. Poor pregnancy outcomes have been described among primary APS pregnancies with hypocomplementemia [19]. The percentage of circulating CD8+DR+ T-cells has been suggested as a biological marker which accurately reflects disease activity in SLE patients [20].…”
Section: Discussionmentioning
confidence: 99%
“…However, a subsequent study failed to report any association between hypocomplementemia and obstetric complications [47]. Conventional treatment of patients with APS during pregnancy can significantly improve live birth rates, so reaching more than 70 % of live birth rate [48], but other complications remain high despite treatment.…”
Section: Authors (Reference) Year Clinical Reports Treatment Protocolmentioning
confidence: 99%